A envergadura constitucional da posse qualificada na desapropriação privada - Araujo Neto, Henrique Batista de (2012)
The constitutionalisation of private relations is the central theme of this work. Approached him overcome the dichotomy between public and private, through functionalization to the constitutionalization of civil law. Research on the effectiveness of horizontal rights. Constitutional under the lens, we analyzed the tense relationship between possession and ownership desfuncionalizada functionalized. We realize that having qualified and gained autonomy, and mechanism of access to goods, in view of the status sheet minimum, and of accomplishment, materializing human dignity. Then, we investigated the expropriation of private ownership qualified as legislative intervention that ensures the enforcement of fundamental rights through the state-court. We face the legal, the constitutionality and the burden of this institute. Also operability that it gives the judge, the process of exercise, the object, issues related to the burden and assessment of damages, as well as the nature, timing and costs of transferring property. At the end, we point to the scarcity palace, as well as the need to repair lege ferenda. The methodological approach has been championed by legal dogmatics in its analytical aspect, as we explore concepts and correlate with our planning. In empirical connotation, we evaluated the normativity and applicability of our law courts. For the ultimate in normative vision, answers to the problems faced and perform the necessary propositions, based on the results from the conceptual and empirical analysis